(untitled) (River Edge, NJ, 2003)
This book covers recent advances in the physics of nucleon resonances, including new experimental results from laboratories in the USA, Europe, and Asia, and new developments in effective field theories, quark models, and lattice gauge theory.
Keywords: Particles (Nuclear physics),Baryons; Congresses,Congresses